When Harry met Sally... [videorecording (Blu-Ray)] - Ephron, Nora; Crystal, Billy; Ryan, Meg; Fisher, Carrie; Kirby, Bruno, 1949-2006; Shaiman, Marc; Sonnenfeld, Barry; Connick, Harry, Jr., 1967-; Connick, Harry, Jr., 1967- ([Publisher not identified], 2011)
"Sex always gets in the way of friendships between men and women. At least, that's what Harry Burns believes. So when Harry meets Sally Albright and a deep friendship blossoms between them, Harry's determined not to let his attraction to Sally destroy it. But when a night of weakness ends in a morning of panic, can the pair avoid succumbing to Harry's fears by remaining friends and admitting they just might be the perfect match for each other?"--Container.